The Relationship between Gestational Weight Gain and Postpartum Depression in Normal and Overweight Pregnant Women. (21st October 2018) - Dayan, Fatemeh; Javadifar, Nahid; Tadayon, Mitra; Malehi, Amal Saki; Komeili Sani, Hosein
Abstract : Objective . To investigate the relationship between weight gain in pregnancy and postpartum depression (PPD) in normal and overweight pregnant women. Methods . The participants of this prospective cohort study were 223 healthy pregnant women with the first trimester body mass index (BMI) between 18.5 and 30 and the gestational age of 10-14 weeks and depressed women were excluded with Beck questionnaire in the first trimester. The evaluation included weight gain at the end of the second and third trimesters and the screening of PPD in 6-8 weeks after delivery by Edinburgh scale. Results . 49 participants were excluded from the study and data from 174 people were analyzed. 32.2% of mothers were scored above 12 in the Edinburgh scale. The only variable associated with depression was the third trimester weight gain (OR 1.17, 95%CI 1.04-1.32). Conclusion . In addition to considering other risk factors for postpartum depression, health care providers should consider the higher probability of PPD in prepregnancy normal and overweight women who have excessive weight gain especially in the third trimester of pregnancy.